Crotoxin from Crotalus durissus terrificus venom: In vitro cytotoxic activity of a heterodimeric phospholipase A2 on human cancer-derived cell lines. (15th December 2018) - Muller, Silvana Pinotti; Silva, Viviane Aline Oliveira; Silvestrini, Ana Vitória Pupo; de Macedo, Luana Henrique; Caetano, Guilherme Ferreira; Reis, Rui Manuel; Mazzi, Mauricio Ventura
Abstract: Crotoxin (CTX), a heterodimeric phospholipase present in venom of snakes of the genus Crotalus, has demonstrated a broad spectrum of pharmacological properties, such as antimicrobial, hemostatic, and antitumoral. However, the precise mechanism of its cytotoxicity and antitumoral properties remains to be determined. Therefore, in the present study, we isolated crotoxin (F1 CTX) through two steps DEAE-Sepharose and Heparin-Sepharose FF chromatography. The C-terminal sequence of the A- and B-chain protein fragment was determined by LC-MS/MS mass spectrometry, which showed 100% identity to crotoxin structure. In order to investigate its cytotoxic effects, we demonstrated that the F1 CTX fraction at 0–30 μg/mL concentrations for 72 h presented a heterogeneous response profile on nine human cancer-derived cell lines from four tumor types (pancreatic, esophagus, cervical cancer, and glioma). The glioma (GAMG and HCB151) and pancreatic (PSN-1 and PANC-1) cancer cells showed a higher sensitivity with IC50 of <0.5, 4.1, 0.7 and < 0.5 μg/mL, respectively. Conversely, F1 CTX does not reduce the viability of normal cells. On the other hand, cervical (SiHa) and esophagus (KYSE270) cancer cell lines presented higher resistance, with IC50 higher than 30.2 and 8.7 μg/mL, respectively. Moreover, F1 CTX did not affect cell cycle distribution under the conditions evaluated and seems to be more cytotoxic than cytostatic. The pro-apoptotic effect of F1 CTX treatment was demonstrated in glioma (HCB151) cell line. In addition, crotoxin revealed a potential to initiate cell responses such as DNA damage in glioma (HCB151) and pancreatic cancer by H2AX activity induction. Conversely, F1 CTX does not reduce the viability of normal cells. Importantly, the comparison of F1 CTX effect with standard chemotherapeutic agents demonstrated a greater cytotoxic potential in the majority of tumor types (glioma, pancreatic, and cervical cancer). On the other hand, F1 CTX was less cytotoxic in esophageal cell lines compared to the gemcitabine agent used in clinical practice. Therefore, this work showed that F1 CTX has a cytotoxic activity and pro-apoptotic potential, contributing to the knowledge about the F1 crotoxin properties as well as its possible use in cancer research, particularly in glioma and pancreatic cancer cell lines. Highlights: Crotoxin demonstrated cytotoxic effect on different tumor cell lines. The molecule had a heterogeneous cytotoxic effect on the different tumor lines. The glioma and pancreatic cancer cells showed a higher sensitivity. Cervical and esophagus cancer cell lines presented higher resistance.